Climate Change-Based Speaking Instructional Material for Students at Saint Paul’s Junior Seminary: Students’ Needs Analysis - Sari, Maria Angela Sylvista; Inderawati, Rita; Amrullah, Amrullah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Through education, awareness of the importance of climate change as a global issue can be delivered. Aligned with the encyclical Laudato si issued by Pope Francis that mentioned climate change, the seminary as a Catholic school is expected to fulfill the Pope's call. This study aimed to determine the needs of Saint Paul's Junior Seminary students to design English speaking materials based on climate change. This study used mixed methods with ADDIE development model. The data was obtained through questionnaires and face-to-face semi-structured interviews. The participants of this research were 31 students of the 4th grade at Saint Paul’s Junior Seminary and an English teacher. The results of the needs analysis showed that: 1) students still had difficulty speaking English; 2) there were no English-speaking materials that specifically discuss climate change; 3) students needed learning resources that provide English language materials that specifically discuss climate change; 4) there should be more practice speaking English about climate change which will increase students' awareness of the environment, in line with Pope Francis' Laudato si. From these needs, it was necessary to develop English-speaking material based on climate change because of the students' inability to speak English about climate change and to increase students’ awareness of climate change.